2016
DOI: 10.3390/ijms17060971
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Mechanisms and Functions of Chemokine (C-X-C Motif) Receptor 4 Heteromerization in Vascular Smooth Muscle

Abstract: Recent evidence suggests that C-X-C chemokine receptor type 4 (CXCR4) heteromerizes with α1A/B-adrenoceptors (AR) and atypical chemokine receptor 3 (ACKR3) and that CXCR4:α1A/B-AR heteromers are important for α1-AR function in vascular smooth muscle cells (VSMC). Structural determinants for CXCR4 heteromerization and functional consequences of CXCR4:α1A/B-AR heteromerization in intact arteries, however, remain unknown. Utilizing proximity ligation assays (PLA) to visualize receptor interactions in VSMC, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 60 publications
(86 reference statements)
4
58
0
Order By: Relevance
“…While the reason for these different dose-responses is unknown, both types have previously been reported in chemotaxis experiments with CXCL12 in human monocytes [2325]. We then tested whether the chemotactic activities can be inhibited with the selective CXCR4 antagonist AMD3100 and with a TM2 peptide analogue of CXCR4, which has previously been shown to inhibit CXCR4 in the human glioblastoma cell line U87 and in primary human monocytes and vascular smooth muscle cells [10, 15, 18, 26]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the reason for these different dose-responses is unknown, both types have previously been reported in chemotaxis experiments with CXCL12 in human monocytes [2325]. We then tested whether the chemotactic activities can be inhibited with the selective CXCR4 antagonist AMD3100 and with a TM2 peptide analogue of CXCR4, which has previously been shown to inhibit CXCR4 in the human glioblastoma cell line U87 and in primary human monocytes and vascular smooth muscle cells [10, 15, 18, 26]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bovine serum albumin, AMD3100, pertussis toxin and U73122 were purchased from Sigma, LY94002 and U0126 from Cell Signaling and 6bK from Tocris. The peptide analogue of transmembrane helix (TM) 2 of CXCR4 (LLFVITLPFWAVDAVANWYFGNDD-NH 2 ) was as described [15]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proximity ligation assays (PLAs) were performed as previously described in detail . In brief, cells were grown and fixed on 8‐well chamber slides (Nunc).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we reported that CXCR4 activation sensitizes α 1 ‐adrenergic receptor (AR) function in vascular smooth muscle and stabilizes blood pressure during the cardiovascular stress response to hemorrhagic shock, whereas activation of ACKR3 inhibits vascular α 1 ‐AR function and impairs blood pressure . Subsequently, we provided evidence that heteromeric complexes between endogenous CXCR4 and α 1A/B ‐AR are constitutively expressed in human vascular smooth muscle cells (hVSMCs), through which CXCR4 modulates α 1 ‐AR function . The molecular mechanisms underlying cross‐talk between ACKR3 and α 1 ‐AR, however, remain elusive.…”
Section: Introductionmentioning
confidence: 99%